Databases in University of Malaya Library system: part II: acquisition and serials activities. - Lee, A. (University of Malaya Library, 1990)
In Part II of this article, the databases for acquisitions and serials activities currently used for housekeeping puposes are examined. The serials module is an in-house developed packae devised to generate relevant information for financial and budgetary control. Similarly, the acquisitions module is an in-house product using dBase III+ and replacing the tedious manual process of repetitive activities in preparing orders and financial management of the book vote. The databases are designed specifically to meet the unique needs of the serials and acquisitions work processes and despite shortcomings and limitations, they have certainly speeded up the work ensuring a more reliable and quicker alternative over the manual method of managing UML's periodical and book votes.